Socio-economic inequalities in stage at diagnosis, and in time intervals on the lung cancer pathway from first symptom to treatment: systematic review and meta-analysis. Issue 5 (28th September 2016) - Forrest, Lynne F; Sowden, Sarah; Rubin, Greg; White, Martin; Adams, Jean
Abstract : Cancer diagnosis at an early stage increases the chance of curative treatment and of survival. It has been suggested that delays on the pathway from first symptom to diagnosis and treatment may be socio-economically patterned, and contribute to socio-economic differences in receipt of treatment and in cancer survival. This review aimed to assess the published evidence for socio-economic inequalities in stage at diagnosis of lung cancer, and in the length of time spent on the lung cancer pathway. MEDLINE, EMBASE and CINAHL databases were searched to locate cohort studies of adults with a primary diagnosis of lung cancer, where the outcome was stage at diagnosis or the length of time spent within an interval on the care pathway, or a suitable proxy measure, analysed according to a measure of socio-economic position. Meta-analysis was undertaken when there were studies available with suitable data. Of the 461 records screened, 39 papers were included in the review (20 from the UK) and seven in a final meta-analysis for stage at diagnosis. There was no evidence of socio-economic inequalities in late stage at diagnosis in the most, compared with the least, deprived group (OR=1.04, 95% CI=0.92 to 1.19). No socio-economic inequalities in the patient interval or in time from diagnosis to treatment were found. Socio-economic inequalities in stage at diagnosis are thought to be an important explanatory factor for survival inequalities in cancer. However, socio-economic inequalities in stage at diagnosis were not found in a meta-analysis for lung cancer. PROSPERO protocol registration number: CRD42014007145.